Penerapan Ajaran Turut Serta Kasus Korupsi Dikaitkan Teori Pertanggungjawaban Pidana - Linda Ulfa; Mohd. Din; Dahlan Dahlan (Kanun Jurnal Ilmu Hukum, 2017)
ABSTRAK: Implementasi penerapan ajaran turut serta dalam kasus tindak pidana korupsi tidak sesuai dengan teori pertanggungjawaban pidana. Hal ini disebabkan penerapan ajaran ini yang tidak sesuai dan tidak memenuhi unsur keadilan. Implikasinya adalah para pelaku tindak pidana korupsi tidak bisa dihukum setimpal dengan apa yang telah diperbuatnya. Selama ini para pelaku tindak pidana korupsi itu dijerat dengan Pasal 55 KUHP yang mengakibatkan pelaku utama tindak pidana korupsi tersebut tidak tersentuh hukum. Upaya hukum yang dapat dilakukan terhadap adanya pelaku lain yang tersangkut dalam tindak pidana korupsi yang sedang diperiksa adalah dengan melakukan penyelidikan dan penyidikan secara mendalam terhadap adanya pelaku baru yang melakukan tindak pidana korupsi tersebut. Pemerintah harus menyempurnakan Undang-Undang Nomor 31 Tahun 1999 Jo Undang-Undang Nomor 20 Tahun 2001 tentang Tindak Pidana Korupsi, agar semua pelaku tindak pidana korupsi dapat tersentuh hukum. Joint Criminal Enterprise Principle Implementation in Corruption Cases Related to Criminal Liability Theories ABSTRACT: The research shows that the implementation of the principle of joint criminal enterprise is not in accordance with theories of criminal responsibility as the implementation is not based on the justice elements, it results from the perpetrators of corruption cases cannot be punished fairly and balanced as what they have committed towards the case of corruption, recently, the corruption perpetrators is imposed by Article 55 of KUHP causing the principals of the corruption case is not being punished. The legal efforts that can be done towards the perpetrators are that are committing the corruption crime that is being investigated are by conducting investigation and the accusation process deeply towards the new perpetrators committing the crime. It proves that the corruption case is committed jointly; hence by finding new suspects would bring justice, usefulness and certainty of laws. It is recommended that the Government of Republic of Indonesia should immediately revise or complement the Act Number 31, 1999 in relation to the Act Number 20, 2001 on the Corruption Crime, hence all the perpetrators of the corruption cases can be punished and touched by the law and there are no one of the perpetrators are free from the imposition of law.